A Decade of Terrorism in the United States and the Emergence of Counter-Terrorism Medicine. Issue 4 (17th August 2021) - Tin, Derrick; Hart, Alexander; Ciottone, Gregory R.
Abstract: Background: The United States (US) is ranked 22 nd on the Global Terrorism Index (2019), a scoring system of terrorist activities. While the global number of deaths from terrorism over the past five years is down, the number of countries affected by terrorism is growing and the health care repercussions remain significant. Counter-Terrorism Medicine (CTM) is rapidly emerging as a necessary sub-specialty, and this study aims to provide the epidemiological context over the past decade supporting this need by detailing the unique injury types responders are likely to encounter and setting the stage for the development of training programs utilizing these data. Methods: The Global Terrorism Database (GTD) was searched for all attacks in the US from 2008-2018. Attacks met inclusion criteria if they fulfilled the three terrorism-related criteria as set by the GTD. Ambiguous events were excluded when there was uncertainty as to whether the incident met all of the criteria for inclusion in the GTD. The grey literature was reviewed, and each event was cross-matched with reputable international and national newspaper sources online to confirm or add details regarding weapon type used and, whenever available, details of victim and perpetrator fatalities and injuries. Results: In total, 304 events were recorded during the period of study. Of the 304 events, 117 (38.5%) used incendiary-only weapons, 80 (26.3%) used firearms as their sole weapon, 55 (18.1%) used explosives, bombs, or dynamite (E/B/D), 23 (7.6%) were melee-only, six (2.0%) used vehicles-only, four (1.3%) were chemicals-only, two (0.7%) used sabotage equipment, two (0.7%) were listed as "others, " and one (0.3%) used biological weapon. There was no recorded nuclear or radiological weapon use. In addition, 14 (4.6%) events used a mix of weapons. Conclusions: In the decade from 2008 through 2018, terrorist attacks on US soil used weapons with well-understood injury-causing modalities. A total of 217 fatal injuries (FI) and 660 non-fatal injuries (NFI) were sustained as a result of these events during that period. Incendiary weapons were the most commonly chosen methodology, followed by firearms and E/B/D attacks. Firearm events contributed to a disproportionality high fatality count while E/B/D events contributed to a disproportionally high NFI count.